Timing of Circulatory and Neurological Events in Syncope - van Dijk, J. Gert; van Rossum, Ineke A.; Thijs, Roland D. (Frontiers in Cardiovascular Medicine, 2020)
Syncope usually lasts less than a minute, in which arterial blood pressure falls enough to cause loss of consciousness before it rises again. The quickest decrease of blood pressure occurs when the heart suddenly stops pumping, which happens in arrhythmia and in severe cardioinhibitory reflex syncope. This causes loss of consciousness in about 8 seconds and a circulatory standstill in 10-15 seconds. A much slower decrease can occur in syncope due to orthostatic hypotension, in which the rate of blood pressure decreases after standing up, so it can stabilise at a low value. Cerebral autoregulation attempts to keep cerebral blood flow constant when blood pressure decreases. In reflex syncope both the quick blood pressure decrease and its low absolute value mean that cerebral autoregulation cannot prevent syncope, whereas it has more protective value in orthostatic hypotension. Neurological signs are related to the severity and timing of cerebral hypoperfusion. Several unanswered pathophysiological questions with possible clinical implications are identified.